Unveiling Shadows: The Impact of Unemployment on Child Maltreatment - Dan Brown; Elisabetta De Cao (Institute of Labor Economics (IZA), 2024)
Child maltreatment is pervasive, often undetected, yet harmful. We investigate whether it is impacted by unemployment by leveraging unique administrative data including all reported cases of child abuse and neglect in the United States from 2004 to 2012. Using an industry shift-share instrument to identify county-level unemployment effects, we find a substantial rise in neglect. The likely channel is lower quality-time spent with children rather than decreased financial investments. Expenditures on children remain stable during recessions. Instead, higher local-area unemployment rate reduces parental childcare time, worsens mental health, and contributes to an increase in one-parent households.
Keywords: I10; D10; J12; J13; K42; 330; child abuse and neglect; unemployment rate; recession; Bartik; mental health